Effectiveness of the SABA Program on Breastfeeding Self-Efficacy and Infant Outcomes in Makassar - Harun, Ayatullah; Ayu Wulandari, Ikrawanty; Dirmansyah Asela, Siti Aisyah Ochin; Nurhasia (Babali Publisher, 2026)
Introduction: Low breastfeeding self-efficacy (BSE) is one of the main barriers to successful exclusive breastfeeding during the first six months of life. The SABA (Sentuhan ASI Bahagia) program was developed as an integrated intervention to strengthen breastfeeding support through education on breastfeeding techniques and training in infant massage. This study aimed to evaluate the effectiveness of the SABA program on BSE, breastfeeding frequency, infant weight, and mothers’ knowledge and skills.Methods: A quasi-experimental pretest–posttest design was conducted with 40 mothers and their infants at the Panambungan Primary Health Center, Mariso District, Makassar City. The research instrument was developed by the researcher and tested for validity and reliability before use during the main data collection. Bivariate analysis was conducted to compare pre-test and post-test values for the variables infant massage knowledge, breastfeeding technique knowledge, infant massage skills, breastfeeding technique skills, breastfeeding self-efficacy (BSE), breastfeeding frequency, and infant weight after the SABA Program intervention.Results: BSE increased significantly after the intervention (p < 0.05). Breastfeeding frequency and infant weight also increased significantly (p < 0.05). In addition, mothers’ knowledge and skills in breastfeeding and infant massage improved significantly (p < 0.05).Conclusion: The SABA program is an effective integrated intervention to enhance BSE and improve breastfeeding outcomes, supporting its integration into breastfeeding support strategies in primary healthcare settings (Puskesmas).Top of Form